Use of late-night salivary cortisol to monitor response to medical treatment in Cushing's disease. Issue 2 (February 2020) - Newell-Price, John; Pivonello, Rosario; Tabarin, Antoine; Fleseriu, Maria; Witek, Przemysław; Gadelha, Mônica R; Petersenn, Stephan; Tauchmanova, Libuse; Ravichandran, Shoba; Gupta, Pritam; Lacroix, André; Biller, Beverly M K
Abstract : Objective: Monitoring of patients with Cushing's disease on cortisol-lowering drugs is usually performed with urinary free cortisol (UFC). Late-night salivary cortisol (LNSC) has an established role in screening for hypercortisolism and can help to detect the loss of cortisol circadian rhythm. Less evidence exists regarding the usefulness of LNSC in monitoring pharmacological response in Cushing's disease. Design: Exploratory analysis evaluating LNSC during a Phase III study of long-acting pasireotide in Cushing's disease (clinicaltrials.gov: NCT01374906). Methods: Mean LNSC (mLNSC) was calculated from two samples, collected on the same days as the first two of three 24-h urine samples (used to calculate mean UFC [mUFC]). Clinical signs of hypercortisolism were evaluated over time. Results: At baseline, 137 patients had evaluable mLNSC measurements; 91.2% had mLNSC exceeding the upper limit of normal (ULN; 3.2 nmol/L). Of patients with evaluable assessments at month 12 ( n = 92), 17.4% had both mLNSC ≤ULN and mUFC ≤ULN; 22.8% had mLNSC ≤ULN, and 45.7% had mUFC ≤ULN. There was high variability in LNSC (intra-patient coefficient of variation (CV): 49.4%) and UFC (intra-patient CV: 39.2%). mLNSC levels decreased over 12 months of treatment and paralleled changes in mUFC. Moderate correlation was seen between mLNSC and mUFC (Spearman's correlation: ρ = 0.50 [all time points pooled]). Greater improvements in systolic/diastolic blood pressure and weight were seen in patients with both mLNSC ≤ULN and mUFC ≤ULN. Conclusion: mUFC and mLNSC are complementary measurements for monitoring treatment response in Cushing's disease, with better clinical outcomes seen for patients in whom both mUFC and mLNSC are controlled.